Molecular Dynamics (MD) Study on the Electrochemical Properties of Electrolytes in Lithium-Ion Battery (LIB) Applications - (:unkn) unknown (My University, 2014)
While the high energy density and the power along with longer cycle life and less requirements of maintenance distinguish the rechargeable lithium-ion batteries (LIBs) from other energy storage devices, development of an electrolyte of LIBs with optimized properties still constitutes a challenge towards next-generation LIB systems with robust electrochemical performance. The electrolytes serve as the medium to provide ionic conduction path between the electrodes as their basic function. Conductivity of the solutions are mainly affected by their transport properties and the electrolyte electrode/separator interfacial phenomena. Although many contributions on thermodynamic properties of the electrolytes consist of alkyl carbonates mixed with salts have been previously studied, relatively little information is known regarding the correlation between interfacial properties of the electrolyte -electrode/separator with electrochemical properties of the cell. In this study, therefore, we present the impacts of salt concentration and temperature-dependent properties of LIBs on wetting behavior of various electrolytes, i.e., ethyl methyl carbonate (EMC), diethyl carbonate (DEC), and propylene carbonate (PC), in contact with the graphite anode and polyethylene (PE)/polypropylene (PP) separator using molecular dynamics (MD) computational technique. The results based on MD computations affirm the general consistent dependency of interfacial tension energies to polarity of the solvents in DEC, EMC, and PC electrolytes contained 1 M LiPF6 salt. The PC systems interestingly showed inverse trend due to the special stacking motifs of PC layers that may increase the interfacial electrostatic interactions. Temperature did not show significant effect on the interfacial energies of linear solvents whereas PC exhibited more tendency to interact with the graphite anode at T = 25 C compared to the similar solution at 0 C. Moreover, the electrolytes that incorporated same solvents had better wettability in absence of salt ions due to their lower polarity and viscosity. Accordingly, EMC: 0.752 M LiPF6 electrolyte system had the lowest interfacial energy value among the EMC solutions contained 1 M and 1.254 M salt. However, the probability of insufficient number of charge carriers in addition to the close values of interfacial energies for electrolytes with 0.752 M and 1 M LiPF6 resulted in considering EMC: 1 M LiPF6 electrolyte as a more efficient mixture. The impact of solution polarity on clustering behavior of the salt ions were investigated in DEC, EMC, and PC electrolytes with 1 M LiPF6 based on the ions coordination and their relative closest neighbors. Due to the higher dielectric constant value, PC showed higher ability of salt dissociating, which leaded that Li+ and PF6- ions were distributed more uniformly compared to the DEC and EMC electrolytes.
Keywords: Electrochemistry; Lithium-Ion Batteries; Molecular Dynamics; Wetting Properties